Alphabet Handwriting Recognition: From Wood‐Framed Hydrogel Arrays Design to Machine Learning Decoding - Yan, Guihua; Hu, Xichen; Miao, Ziyue; Liu, Yongde; Zeng, Xianhai; Lin, Lu; Ikkala, Olli; Peng, Bo (Advanced science, 2024)
Handwriting recognition is a highly integrated system, demanding hardware to collect handwriting signals and software to deal with input data. Nonetheless, the design of such a system from scratch with sustainable materials and an easily accessible computing network presents significant challenges. In pursuit of this goal, a flexible, and electrically conductive wood‐derived hydrogel array is developed as a handwriting input panel, enabling recognizing alphabet handwriting assisted by machine learning technique. For this, lignin extraction‐refill, polypyrrole coating, and polyacrylic acid filling, endowing flexibility, and electrical conduction to wood are sequentially implemented. Subsequently, these woods are manufactured into a 5 × 5 array, creating a matrix of signals upon handwriting. Efficient handwritten recognition is then achieved through appropriate manual feature extraction and algorithms with low complexity within a computing network, as demonstrated in this work, the strategic choice of expertise‐based feature engineering and simplified algorithms effectively boost the overall model performance on handwriting recognition. With potential adaptability, further applications in customized wearable devices and hands‐on healthcare appliances are envisioned. A flexible and electrically conductive wood‐derived hydrogel array is designed as a handwriting input panel, enabling alphabet handwriting recognition assisted by machine learning technique. This work promotes sustainable manufacture in customized wearable devices and hands‐on healthcare appliances.